2022
DOI: 10.1186/s13568-022-01461-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting endophytic fungi for antifeedants and larvicides and their enhancement by gamma irradiation

Abstract: The search and discovery of new natural products with antifeedant and larvicidal potentials to mitigate harmful insects are scientific pressing issues in the modern agriculture. In this paper, the antifeedant and larvicidal potentials of 69 fungal isolates were screened against the Egyptian cotton leafworm Spodoptera littoralis. A total of 17 isolates showed the insecticidal potentials with three promising isolates. These strains were Aspergillus sydowii, Lasiodiplodia theobromae, and Aspergillus flavus isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…In literature, several reports recommend gamma rays as a physical mutagen for the improvement of microbial cultures to intensify their production abilities 32 34 . It is noteworthy that, this improvement of microbial cultures using gamma irradiation mutagenesis could lead to the isolation of hyper-producers thereby lowering the overall cost of the process 35 – 38 .…”
Section: Resultsmentioning
confidence: 99%
“…In literature, several reports recommend gamma rays as a physical mutagen for the improvement of microbial cultures to intensify their production abilities 32 34 . It is noteworthy that, this improvement of microbial cultures using gamma irradiation mutagenesis could lead to the isolation of hyper-producers thereby lowering the overall cost of the process 35 – 38 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, bioprospecting of fungal endophytes for new compounds has attracted greater attention 10 , 11 . Generally, endophytes proved to be excellent and sustainable sources of many bioactive compounds with potential applications in pest control 12 , bio-pigment production 13 , antibiotics 14 , antioxidant and antimycotic activities 15 , manufacturing terpenoids and other volatile organic compounds 16 , 17 , food industry, and other pharmaceutical industry 18 . Strobel et al, also demonstrated that certain endophytic fungi can introduce to alternative and sustainable sources of fuel-related hydrocarbons 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their numerous biotechnological applications, as well as their affordability and ease of use as a culture medium for, say, the development and metabolism of fungi, cells have garnered a lot of interest [4]. In an effort to discover new compounds with a range of functions, recent research has concentrated on bioprospecting endophytic fungi, or the fungi that reside inside plant tissues [5][6][7]. Endophytic fungi have mainly been examined as producers of innovative bioactive substances and additional metabolic products from plant hosts [8][9][10].…”
Section: Introductionmentioning
confidence: 99%